Sustainable Planning and Development of Smart City: A Structured Literature Review - Aji, Gumiwang Restu; Hijri, Yana Syafriyana; Salahudin, Salahudin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to provide a more detailed understanding of smart city sustainable development planning using a systematic literature review method, by re-reading previous research studies that are deemed relevant to the discussion of the theme of Planning and Sustainable Development. Articles are taken from publications of various publishers using the SCOPUS database and are given a limitation of the year of publication within 2020. The results of this study display 270 articles that are relevant to the topic of this research. The figure is obtained from the number of (.ris)-formed files which is exported to Mendeley software. Then a paper review is done to see the shortcomings of previous research so that improvements can be made to make the discussion more structured, starting from planning to implementation. The limitation of this research is that the examples of articles presented are different from the conditions that exist in each country, so there needs to be a critical understanding of the government system in the examples that are used as references. Other than that, special considerations are needed in determining equations and new discoveries from articles that are used as reference to develop the main idea according to the chosen topic and title.